Porous aluminum foil, preparation method and counter electrode
The nanofiber membrane/aluminum foil composite was prepared through electrospinning and electrostatic spraying technology, and the porous aluminum foil was formed through the sintering process, which solved the problems of serious pollution and low efficiency in the existing technology, and achieved efficient and environmentally friendly porous aluminum foil preparation, improving the uniformity and production efficiency of the product.
Patent Information
- Application Number
- CN202411631548.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
AI Technical Summary
The existing porous aluminum foil preparation technology has problems such as serious pollution, low efficiency and poor controllability, and it is difficult to adapt to large-scale industrial production.
The precursor nanofiber membrane/aluminum foil composite was prepared by electrospinning and electrostatic spraying technology, and porous aluminum foil with uniform pore structure was formed through the sintering process.
It improves the uniformity and production efficiency of porous aluminum foil, improves product quality, and has environmentally friendly and energy-saving processes, making it suitable for large-scale industrial production.
Smart Images

Figure CN119601671A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum foil material preparation, and is applied to the field of lithium metal batteries, and specifically to a preparation method of a porous aluminum foil and its application. Background Art
[0002] Aluminum as a negative electrode material for lithium-ion batteries has a high theoretical capacity (about 2980 mAh g -1 ) and a low and safe charging and discharging platform, and its reserves are abundant, the cost is low, and it is of great research and application value. However, the application of aluminum negative electrode materials for lithium-ion batteries faces serious challenges. On the one hand, the surface of aluminum materials is very easy to oxidize, which affects its electrochemical activity and leads to low actual capacity; on the other hand, the huge volume expansion of aluminum powder easily causes it to pulverize and lose contact with the current collector, resulting in serious voltage decay. Through the overall structural design, it is expected to reduce the surface area of aluminum negative electrode, thereby effectively inhibiting its surface oxidation and improving its lithium storage activity. At the same time, the overall structure can enhance the mutual contact between local aluminum materials, improve the overall structural stability, and improve the cycle performance. Aluminum foil as a self-supporting lithium-ion battery negative electrode shows good electrochemical performance, which is significantly better than ordinary aluminum powder particle negative electrode materials. The disadvantage is that the electrolyte has low wettability with aluminum foil, which makes it difficult to fully and efficiently exert the lithium storage activity of aluminum foil. If a three-dimensional porous aluminum foil structure can be designed, it is expected to effectively improve the electrolyte wettability and significantly improve its performance. At present, the traditional preparation process of porous aluminum foil includes electrochemical corrosion and high-temperature sintering. The electrochemical corrosion method is more polluting, and the surface of the aluminum foil is easily oxidized in a liquid environment, which affects its electrochemical activity. The sintering method mainly increases the specific surface area by sintering aluminum powder to the surface of the aluminum film, but the existing sintering method has problems such as low efficiency and poor controllability, and is difficult to adapt to large-scale industrial production. Therefore, it is of great significance to develop a method for preparing porous aluminum foil with simple process, low cost and controllable structure. Summary of the invention
[0003] The present invention provides a new method for preparing porous aluminum foil, which prepares a precursor nanofiber membrane / aluminum foil composite by electrospinning and electrostatic spraying technology, and then forms a porous aluminum foil with a uniform pore structure by a sintering process, aiming to solve the shortcomings of the existing porous aluminum foil preparation technology and improve the uniformity, production efficiency and product quality of the porous aluminum foil. Here, we directly use porous aluminum foil as the negative electrode / counter electrode material, provide a simplified manufacturing process, and eliminate conductive additives, binders and casting procedures. This not only marks a pioneering application in porous aluminum foil negative electrodes, but also demonstrates the great potential for developing low-cost and high-energy porous aluminum foil-based lithium batteries.
[0004] Technical Solution The technical solution of the present invention comprises the following steps: (1) Preparation of electrospinning solution: First, a certain amount of organic solvent is measured, and then a certain amount of polymer powder is weighed and placed in the organic solvent. The solution is stirred magnetically for a certain period of time to form a uniform and transparent electrospinning solution, which is referred to as solution A. Preparation of electrostatic spray solution: First, a certain amount of alcohol solution is measured, and then a certain amount of nitrate is weighed and placed in ethylene glycol. The solution is stirred magnetically for a certain period of time to form a colorless and transparent liquid, which is referred to as solution B.
[0005] (2) Preparation of nanofiber membrane / aluminum foil composite by combining electrospinning and electrostatic spraying: The prepared solution A is placed in a syringe, and the solution B is placed in a syringe. Solution A is electrospun and solution B is electrostatically sprayed. During the electrospinning and electrostatic spraying process, the metal needle of the syringe is connected to the high-voltage positive electrode (the metal needles of the two syringes are in the same parallel position and connected to the high-voltage positive electrode), and the aluminum foil is connected to the negative electrode as the receiving end. A high-voltage direct current is applied between the two electrodes. During the electrospinning and electrostatic spraying process, the electrospun fibers come into contact with the mist particles of the electrostatic spray, forming a nanofiber membrane deposited on the aluminum foil, thereby obtaining a precursor nanofiber membrane / aluminum foil composite.
[0006] (3) Drying the precursor nanofiber membrane / aluminum foil composite to remove the solvent.
[0007] (4) Heat treating (3): placing the prepared nanofiber membrane / aluminum foil composite in air, vacuum or inert gas (such as nitrogen, argon) for heat treatment to decompose or carbonize the polymer, thereby forming a porous structure on the surface of the aluminum foil.
[0008] Compared with the prior art, the advantages and beneficial effects of the present invention are: (1) Improving the uniformity of porous aluminum foil: The nanofiber membrane prepared by electrospinning and electrostatic spraying technology has a high degree of uniformity and controllability, making the pore structure of the porous aluminum foil more uniform.
[0009] (2) Improve production efficiency: The combination of electrospinning / spraying technology and sintering process realizes the continuous preparation of porous aluminum foil, greatly improving production efficiency.
[0010] (3) Improving product quality: By optimizing the electrospinning / spraying solution formula, spinning parameters and sintering process conditions, porous aluminum foil with excellent mechanical and electrochemical properties can be prepared.
[0011] (4) Environmental protection and energy saving: Compared with the traditional electrochemical corrosion method, the method of combining electrospinning / spraying technology with sintering process adopted in the present invention is more environmentally friendly and energy-saving, and reduces the emission of pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The present invention will be further described below in conjunction with the accompanying drawings.
[0013] Figure 1 (a) Optical photograph of nanofiber membrane / aluminum foil composite prepared by combining electrospinning and electrostatic spraying; (b) Optical photograph of precursor nanofiber membrane / aluminum foil composite; (c) Optical photograph of the homemade background light irradiation device required for photographing electrode materials.
[0014] Figure 2 Optical photographs of the materials prepared in Example 1: (a) optical photograph of the porous aluminum foil and the nitrate-containing nanofiber membrane after sintering; (b) optical photograph of the porous aluminum foil after slicing; (c) optical photograph of the porous aluminum foil under light irradiation.
[0015] Figure 3 XRD pattern of the porous aluminum foil prepared in Example 1.
[0016] Figure 4 SEM images of the materials prepared in Example 1: (a) low-magnification SEM image of porous aluminum; (b) high-magnification SEM image of porous aluminum; (c) SEM image of the nitrate-containing nanofiber membrane.
[0017] Figure 5 Optical photographs of the materials prepared in Example 2: (a) optical photograph of the porous aluminum foil after sintering; (b) optical photograph of the porous aluminum foil after slicing; (c) optical photograph of the porous aluminum foil under light irradiation.
[0018] Figure 6 XRD pattern of the porous aluminum foil prepared in Example 2.
[0019] Figure 7 SEM image of the porous aluminum foil prepared in Example 2.
[0020] Figure 8 Example 3 Aluminum current collector: (a) optical photograph after slicing; (b) optical photograph under light irradiation; (c) XRD image; (d) SEM image.
[0021] Fig. 9 Example 4 Spun aluminum foil: (a) optical photograph after slicing; (b) optical photograph under light irradiation; (c) XRD image; (d) SEM image.
[0022] Fig.10 Example 5 Commercial porous aluminum foil: (a) optical photograph after slicing; (b) optical photograph under light irradiation.
[0023] Fig.11 Optical photograph of Example 6 directly sintered from aluminum current collector.
[0024] Fig.12Optical photograph of Example 7 obtained by sintering the aluminum current collector directly under argon atmosphere.
[0025] Fig.13 Optical photographs of the material prepared in Example 8: (a) optical photograph after slicing; (b) optical photograph under light irradiation; (c) SEM image.
[0026] Fig.14 Optical photographs of the material prepared in Example 9: (a) optical photograph after pre-oxidation; (b) optical photograph after annealing in argon atmosphere.
[0027] Fig.15 Contact angle test pictures of Example 1, Example 3 and Example 5.
[0028] Fig.16 Electrochemical performance diagrams of the embodiments: (a) charge-discharge curve diagram of the first three cycles of embodiment 1; (b) charge-discharge curve diagram of the first three cycles of embodiment 2; (c) cycle efficiency diagram of the embodiments.
[0029] Fig.17 The first three charge and discharge curves of the embodiment. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the following embodiments will further illustrate the present invention in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. On the contrary, the present invention covers any substitutions, modifications, equivalent methods and schemes made on the essence and scope of the present invention as defined by the claims. Further, in order to enable the public to have a better understanding of the present invention, some specific details are described in detail in the following detailed description of the present invention. For those skilled in the art, the present invention can be fully understood without the description of these details.
[0031] The present invention provides a porous aluminum foil, wherein the porous aluminum foil has a pore structure accounting for 10-50% of the surface area, a pore diameter of 0.8-5.5 μm, and a pore area of 7.8-305 μm. 2 .
[0032] Preferably, the porous aluminum foil is obtained by sintering a nitrate-containing nanofiber membrane deposited on the aluminum foil.
[0033] Preferably, the aluminum foil is selected from current collector aluminum foil or spinning aluminum foil.
[0034] Preferably, in some embodiments, the nitrate includes any one or more of copper nitrate, gallium nitrate, bismuth nitrate, zinc nitrate, aluminum nitrate, germanium nitrate, cobalt nitrate, manganese nitrate, molybdenum nitrate, and nickel nitrate.
[0035] Preferably, the nitrate-containing nanofiber membrane is a nitrate-containing nanofiber membrane layer material formed by relative contact between a polymer solution through electrostatic spinning and a nitrate solution through electrostatic spraying.
[0036] Preferably, the deposition is a process in which a high molecular polymer solution is electrospun and a nitrate solution is electrostatically sprayed and brought into relative contact, and then deposited on an aluminum foil to form a nitrate-containing nanofiber membrane material.
[0037] Preferably, the spinning equipment is SS-1 type produced by Beijing Yongkang Leye Technology Development Co., Ltd.
[0038] Preferably, in some embodiments, the polymer solution is selected from any one of polyvinylidene fluoride PVDF, polyacrylonitrile PAN, polyvinyl pyrrolidone PVP, polystyrene PS, polyvinyl fluoride PTFE, and polychloroprene CR, and the solution is formed after dissolving in an organic solvent, and the organic solvent is selected from any one of N,N-dimethylformamide DMF, ethanol, acetonitrile ACN, acetone ACE, and cyclopentane sulfone TMS.
[0039] Preferably, in some embodiments, the nitrate solution includes a solution formed by dissolving any one or more of copper nitrate, gallium nitrate, bismuth nitrate, zinc nitrate, aluminum nitrate, germanium nitrate, cobalt nitrate, manganese nitrate, molybdenum nitrate, and nickel nitrate in an alcohol solution, and the alcohol solution is selected from ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, butanetriol, sec-butanol, and tert-butanol.
[0040] Among them, nitrate solution can improve the dispersion and uniformity of fibers, avoid the occurrence of fiber bundles or agglomeration during the spinning process, and increase the crystallinity of polymer-based fibers, thereby improving their mechanical strength and toughness. During the electrostatic spraying process, nitrate solution usually has a strong electrical conductivity, which helps to improve the current efficiency of the liquid, ensure the good formation and dispersion of the spray particles, and the ions in the solution can participate in the interaction of polymer chains, promote the cross-linking and film-forming process of the polymer, thereby improving the density and stability of the film. Compared with nitrates, other salts have low electrical conductivity and poor solubility, which is not conducive to film formation and performance improvement.
[0041] Preferably, the method for preparing the porous aluminum foil comprises the following steps: (1) Preparation of electrospinning solution: The polymer is dissolved in an organic solvent, referred to as solution A. Preparation of electrostatic spray solution: nitrate was dissolved in alcohol solution, denoted as solution B; (2) Preparation of nanofiber membrane by combining electrospinning and electrostatic spraying: The prepared electrospinning solution is placed in a 5 mL syringe, and the electrostatic spray solution is placed in a 2.5 mL syringe. The metal needle of the syringe is connected to the high-voltage positive electrode (the metal needles of the two syringes are in the same parallel position and connected to the high-voltage positive electrode). The aluminum foil is used as the receiving end to connect the negative electrode. A high-voltage direct current is applied between the two electrodes. During the electrospinning and electrostatic spraying process, the electrospun fibers come into contact with the mist particles of the electrostatic spray, forming a nanofiber membrane deposited on the aluminum foil, thereby obtaining a precursor nanofiber membrane / aluminum foil composite. (3) Drying and heat treating the precursor nanofiber membrane / aluminum foil composite to form a porous structure on the surface of the aluminum foil.
[0042] Preferably, in the method for preparing the porous aluminum foil, the polymer solution is selected from any one of polyvinylidene fluoride PVDF, polyacrylonitrile PAN, polyvinyl pyrrolidone PVP, polystyrene PS, polyvinyl fluoride PTFE, and polychloroprene CR, and the solution is formed by dissolving the solution in an organic solvent, the organic solvent is selected from any one of N,N-dimethylformamide DMF, ethanol, acetonitrile ACN, acetone ACE, and cyclopentane sulfone TMS, and the mass fraction of the polymer solution is 10-15%.
[0043] Preferably, in the method for preparing the porous aluminum foil, the nitrate solution includes a solution formed by dissolving any one or more of copper nitrate, gallium nitrate, bismuth nitrate, zinc nitrate, aluminum nitrate, germanium nitrate, cobalt nitrate, manganese nitrate, molybdenum nitrate, and nickel nitrate in an alcohol solution, and the alcohol solution is selected from ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, butanetriol, sec-butanol, and tert-butanol, and the mass concentration is 99.7% (analytical grade).
[0044] Preferably, in the preparation method of the porous aluminum foil, the electrospinning solution is placed in a 5 mL syringe, and the spinning conditions are: temperature of 40-55°C, humidity of 35-45%, spinning at a voltage of 12-18 kV, and a receiving distance of 10-18 cm, and electrospinning for 10-24 hours; the electrostatic spray solution is placed in a 2.5 mL syringe, and the spraying conditions are: temperature of 40-55°C, humidity of 35-45%, electrostatic spraying at a voltage of 12-18 kV, and a receiving distance of 10-18 cm, and electrostatic spraying for 10-24 hours.
[0045] Preferably, in the method for preparing the porous aluminum foil, the heat treatment is pre-sintering in an air atmosphere at 1-3°C min -1 The heating rate is 250-300 °C for 1-3 hours, and then heated at 3-5 °C min in an argon atmosphere. -1The heating rate is 600-800℃ and calcined for 2-5 hours.
[0046] Preferably, in the method for preparing the porous aluminum foil, during the sintering process, the nanofiber membrane / aluminum foil composite material is clamped by a graphite plate for heat treatment.
[0047] During the heat treatment process, the prepared nanofiber membrane / aluminum foil composite is placed in air, vacuum or inert gas (such as nitrogen, argon) for heat treatment to decompose or carbonize the polymer, which serves as a template for melting and reconstructing the aluminum foil, thereby forming a porous structure on the surface of the aluminum foil.
[0048] For those skilled in the art, it is inevitable to separate the products after the heat treatment, that is, to separate the carbon nanofibers and the porous aluminum foil, and to perform subsequent treatments such as cleaning and drying on the porous aluminum foil, so as to finally obtain a high-performance aluminum foil with a uniform porous structure.
[0049] Another technical solution of the present invention is to provide an application of the porous aluminum foil, that is, an application as a counter electrode of a lithium metal battery.
[0050] A counter electrode of a lithium metal battery comprises the porous aluminum foil.
[0051] Based on the above technical solution, the present invention also provides a lithium battery, comprising a lithium sheet and a separator, and also comprising a porous aluminum foil disposed under the separator as a counter electrode.
[0052] The present invention adopts electrospinning and electrostatic spraying technology to prepare the precursor nanofiber membrane / aluminum foil composite (optical photos of materials prepared by electrospinning and electrostatic spraying technology are shown in Figure 2). Figure 1 The optical photograph of the obtained precursor nanofiber membrane / aluminum foil composite is shown in a. Figure 1 b), and then a porous aluminum foil with a uniform pore structure is formed through a sintering process, which is more conducive to the deposition and dispersion of lithium. Compared with ordinary aluminum foil, it has better cycle stability. The preparation process of the present invention is green and environmentally friendly, the reaction process is controllable, the process is simple, the preparation cycle is short, the cost is low, and the prepared porous aluminum foil shows excellent lithium negative electrode protection performance in lithium metal batteries. The lithium metal battery using this porous aluminum foil shows excellent cycle stability performance, which is expected to promote the practical application of lithium metal batteries. (Optical photograph of the homemade background light irradiation device required for shooting electrode materials is shown in Figure 2) Figure 1 c).
[0053] Example 1 First, weigh 1.3 g of polyacrylonitrile (PAN) and add it to 10 mL of N,N-dimethylformamide (DMF) and stir for 48 hours to obtain a colorless transparent solution, which is solution A. Then weigh 0.1 g of bismuth nitrate (Bi(NO3)3· 5H2O) was stirred in 5 mL of ethylene glycol for 48 h to form a colorless transparent liquid, which was used as solution B.
[0054] The precursor A solution was transferred into a syringe with a nozzle diameter of 0.33 mm and a capacity of 5 mL, and the precursor B solution was transferred into a syringe with a nozzle diameter of 0.33 mm and a capacity of 2.5 mL. The aluminum current collector was used as the receiving end for double needle blending. The positive voltage was 15 kV, the negative voltage was 3 kV, the temperature was 45 °C, the humidity was 35 ± 5%, the receiving distance was 15 cm, and the injection rate was 0.42 mL h -1 The collected products were dried in an oven at 60 °C for 18 h to obtain a precursor nanofiber membrane / aluminum foil composite.
[0055] Then, the precursor nanofiber membrane / aluminum foil composite was heated at 1°C min in air atmosphere. -1 The pre-oxidation was carried out at 250 °C for 3 h and then heated at 5 °C min -1 The porous aluminum foil and nitrate-containing nanofiber membrane materials were obtained by annealing at 700 °C for 3 h at a heating rate of 1.5 ℃. Figure 2 a). The obtained material was cut into discs with a diameter of 14 mm ( Figure 2 b), the surface presents an irregular texture with high surface roughness; Figure 2 c is an optical photograph under light irradiation, from which it can be seen that the prepared material is light-transmissive. The sintered material was analyzed by XRD spectrum, and the obtained diffraction peaks corresponded well to Al (PDF#85-1327) ( Figure 3 The obtained samples were tested by scanning electron microscope (SEM). Figure 4 As shown in a, the sample presents a distinct rough and irregular flake-like structure. This unique surface morphology reflects rich texture features, indicating that the surface roughness of the material is high. As the magnification increases ( Figure 4 b), the surface profile of the sample showed smoother features, indicating a higher density. In addition, the microscopic image showed that some areas had pore structures accounting for 30-50% of the surface area, 1.27-25.61 μm, and pore areas of 5.13-682.65 μm 2 This further proves the characteristics of the porous aluminum foil and suggests that it has good electrolyte wettability and a large specific surface area. In summary, the successful preparation of the porous aluminum foil is shown, which may lay the foundation for subsequent research and practical applications. In addition, the nitrate-containing nanofiber membrane ( Figure 4c), we found that the nanofibers in the membrane were randomly interwoven, showing a dense network structure, and the diameter of the nanofibers was about 42.94-67.99 nm. The mist particles prepared by electrostatic spraying were also found from the figure, with a particle size range of 29-77 nm.
[0056] The materials were made into batteries as follows: porous aluminum foil was used as the negative electrode / counter electrode, Celgard 2400 microporous polypropylene was used as the separator, 1 M LiTFSI was dissolved in DME+DOL (volume ratio of 1:1) solution and 2% LiNO3 additive was used as the electrolyte, and metal lithium sheets were assembled into CR2025 button cells in an argon-protected glove box. After all the batteries were assembled, they were left to stand for 8 hours and then the electrochemical performance was tested using the LAND CT2001A battery test system.
[0057] Example 2 In this example, the aluminum current collector in Example 1 is used as the receiving end instead of a spun aluminum foil (aluminum content 98.79%). The battery assembly and testing methods are exactly the same as those in Example 1. The optical photograph of the material after sintering is shown in FIG. Figure 5 As shown in a, the prepared material was cut into discs with a diameter of 14 mm ( Figure 5 b), the surface also presents an irregular texture; it is also translucent when exposed to light ( Figure 5 c). The prepared material was analyzed by XRD spectrum, and the obtained diffraction peaks corresponded well to Al (PDF#85-1327) ( Figure 6 ). The material is subjected to SEM test, such as Figure 7 As shown in the figure, it can be seen that the surface of the obtained sample is relatively smooth and has a pore structure with a pore diameter of 0.8-5.5 μm and a pore area of 7.8-305 μm 2 In summary, it shows that the porous aluminum foil was successfully prepared.
[0058] Example 3 In this example, the porous aluminum foil prepared in Example 1 was replaced with an Al current collector, and the battery assembly and testing methods were exactly the same as those in Example 1. The optical photograph of the Al current collector after slicing is shown in FIG. Figure 8 As shown in a, the untreated Al current collector is not light-transmissive under light irradiation ( Figure 8 b). Perform XRD analysis on it, such as Figure 8 c shows that the obtained diffraction peak corresponds well to Al (PDF#85-1327). SEM test shows that the surface of Al current collector is smooth and the filamentary lines are regularly arranged. The lines are normal metal stripes ( Figure 8 d) Example 4 In this example, the porous aluminum foil prepared in Example 1 was replaced with a spun aluminum foil. The battery assembly and testing methods were exactly the same as those in Example 1. Fig. 9 As shown in a, the untreated spun aluminum foil is not light-transmissive when exposed to light ( Fig. 9 b). Perform XRD analysis on it, such as Fig. 9 c shows that the obtained diffraction peak corresponds well to Al (PDF#85-1327). Through SEM testing, it was found that the surface of the spun aluminum foil was relatively smooth, with a few slight protrusions on the surface, which is a normal phenomenon caused by the production process ( Fig. 9 d) Example 5 In this example, the porous aluminum foil prepared in Example 1 was replaced with a commercial porous aluminum foil (Desco Electronic Technology (Kunshan) Co., Ltd.). The battery assembly and testing methods were exactly the same as those in Example 1. The optical photograph of the commercial porous aluminum foil after slicing is shown in FIG. Fig.10 As shown in a, commercial porous aluminum foil has a certain light transmittance under light irradiation ( Fig.10 b).
[0059] Example 6 In this embodiment, only the sintered sample in Example 1 (the precursor nanofiber membrane / aluminum foil composite obtained in Example 1) is changed to a pure Al current collector. Fig.11 It can be observed from the optical photos that the obtained material is not tough enough and is very easy to break, so it cannot be directly assembled into batteries.
[0060] Example 7 In this embodiment, the Al current collector is directly heated in an argon atmosphere at 5 °C min -1 The heating rate is annealed at 700 °C for 3 h (without air atmosphere pre-oxidation sintering process). Fig.12 It can be observed that the obtained porous aluminum foil is very easy to break, so it cannot be directly assembled into a battery.
[0061] Example 8 In this example, only the B solution in Example 1 was changed to ethylene glycol (without bismuth nitrate), and the battery assembly and testing methods were exactly the same as those in Example 1. The optical photograph of the obtained material after sintering is shown in FIG. Fig.13 As shown in a, the prepared material is found to be light-transmissive under light irradiation ( Fig.13 b) Through SEM testing, it was found that the surface of the prepared material was rough and showed an irregular morphology, and its surface was covered with irregular textures ( Fig.13 c).
[0062] Example 9 This example only uses the electrostatic spinning of solution A in Example 1. The optical photograph of the material obtained after sintering is as follows Fig.13 As shown in the figure, due to the lack of electrostatic spraying of solution B, the spinning precursor and the Al current collector cannot fit closely together. During the sintering process, the carbon material will shrink. The optical photograph after pre-oxidation is as shown in Fig.14 As shown in a, the temperature was 5 °C min under argon atmosphere. -1 The optical photograph after annealing at 700 °C for 3 h is shown in Fig.14 As shown in b, the surface of the prepared material is relatively smooth and thin, and it cannot be sliced, so the battery cannot be assembled.
[0063] Example 10 In this embodiment, only the polymer in Example 1 is changed to polyvinyl pyrrolidone (PVP), and the battery assembly and testing methods are exactly the same as those in Example 1.
[0064] Embodiment 11 In this embodiment, only the alcohol solution in Example 1 is replaced with propylene glycol, and the battery assembly and testing methods are exactly the same as those in Example 1.
[0065] Example 12 In this example, only the organic solvent in Example 1 is changed to acetonitrile ACN, and the battery assembly and testing methods are exactly the same as those in Example 1.
[0066] Example 13 In this embodiment, only the bismuth nitrate in Embodiment 1 is replaced with zinc nitrate, and the battery assembly and testing methods are exactly the same as those in Embodiment 1.
[0067] Embodiment 14 In this embodiment, only the bismuth nitrate in Example 1 is replaced with cobalt nitrate, and the battery assembly and testing methods are exactly the same as those in Example 1.
[0068] The contact angle test was conducted on Example 1, Example 3 and Example 5. The prepared porous aluminum foil was cleaned and a certain volume of electrolyte was dripped onto the surface of the porous aluminum foil using a micropipette. After the droplet was stable, the contact angle measuring instrument Theta Lite was used to take an image of the droplet and the contact angle was automatically measured by the software analysis system. The analysis results are shown in Table 1. Fig.15 As shown, the porous aluminum foil prepared by Example 1 can reduce the contact angle of the electrolyte from 43.54° to about 20.24° (and less than the contact angle of 32.37° of the commercial porous aluminum foil), indicating that the surface energy of the porous aluminum foil is increased and the surface roughness may also be increased, thereby improving the wettability of the electrolyte.
[0069] Electrochemical performance analysis: Electrochemical performance tests were performed using the LAND CT2001A battery testing system. Fig.16a and b are the charge and discharge curves of the lithium metal battery of the materials prepared in Example 1 and Example 2, respectively. The horizontal axis represents the mass capacity and the vertical axis represents the voltage. The porous aluminum foil prepared in Examples 1 and 2 has a significantly improved initial efficiency compared to the aluminum current collector in Example 3 (0.21%). Fig.16 c, the horizontal axis represents the number of cycles, and the vertical axis represents the coulombic efficiency. The results show that the nanofiber membrane / aluminum foil composite was pre-oxidized at 250 °C for 3 h and annealed at 700 °C in an argon atmosphere for 3 h. The battery assembled with 1M LiTFSI dissolved in DME+DOL (volume ratio of 1:1) and 2% LiNO3 as an additive has better performance at a current density of 0.5 A g -1 Mass capacity is 600 mAh g -1 Under almost all conditions, they can be cycled for 200 cycles. However, the aluminum current collector in Example 3 began to irreversibly decay after 28 cycles. The spun aluminum foil in Example 4 began to decay after 31 cycles. The commercial aluminum foil in Example 5 began to decay after about 40 cycles. In Example 8, the material prepared in which solution B did not contain bismuth nitrate began to decay after 90 cycles. In summary, the precursor nanofiber membrane / aluminum foil composite prepared by combining electrospinning and electrostatic spraying technology, and then the porous aluminum foil prepared by sintering process has excellent electrochemical properties. Fig.17 It is the charge and discharge curve diagram of the first three cycles of the embodiment.
Claims
1. A porous aluminum foil, characterized in that: The porous aluminum foil has a pore structure accounting for 10-50% of the surface area, a pore diameter of 0.8-5.5 μm, and a pore area of 7.8-305 μm. 2 .
2. The porous aluminum foil according to claim 1, characterized in that The porous aluminum foil is obtained by sintering a nitrate-containing nanofiber membrane deposited on the aluminum foil.
3. The porous aluminum foil according to claim 2, characterized in that The nitrate includes any one or more of copper nitrate, gallium nitrate, bismuth nitrate, zinc nitrate, aluminum nitrate, germanium nitrate, cobalt nitrate, manganese nitrate, molybdenum nitrate and nickel nitrate.
4. The porous aluminum foil according to claim 3, characterized in that The nitrate-containing nanofiber membrane is a nitrate-containing nanofiber membrane layer material formed by relative contact between a high molecular polymer solution through electrostatic spinning and a nitrate solution through electrostatic spraying.
5. The porous aluminum foil according to claim 4, characterized in that The deposition is a process in which a high molecular polymer solution is electrostatically spun and a nitrate solution is electrostatically sprayed, and then brought into relative contact and deposited on an aluminum foil to form a nanofiber membrane material containing nitrate.
6. The porous aluminum foil according to claim 5, characterized in that The high molecular polymer solution is a solution formed by dissolving any one of polyvinylidene fluoride PVDF, polyacrylonitrile PAN, polyvinyl pyrrolidone PVP, polystyrene PS, polyvinyl fluoride PTFE, and polychloroprene CR in an organic solvent, and the organic solvent is selected from any one of N,N-dimethylformamide DMF, ethanol, acetonitrile ACN, acetone ACE, and cyclopentane sulfone TMS.
7. The porous aluminum foil according to claim 5, characterized in that The nitrate solution includes a solution formed by dissolving any or more of copper nitrate, gallium nitrate, bismuth nitrate, zinc nitrate, aluminum nitrate, germanium nitrate, cobalt nitrate, manganese nitrate, molybdenum nitrate, and nickel nitrate in an alcohol solution, and the alcohol solution is selected from ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, butanetriol, sec-butanol, and tert-butanol.
8. A method for preparing a porous aluminum foil, characterized in that: The steps include: (1) Preparation of electrospinning solution: The polymer is dissolved in an organic solvent, referred to as solution A. Preparation of electrostatic spray solution: nitrate was dissolved in alcohol solution, denoted as solution B; (2) Preparation of nanofiber membrane by combining electrospinning and electrostatic spraying: The prepared electrospinning solution is placed in one syringe, and the electrostatic spray solution is placed in another syringe. The metal needles of the two syringes are connected to the high-voltage positive electrode, and the metal needles of the two syringes are in the same parallel position. The aluminum foil is used as the receiving end to connect the negative electrode. A high-voltage direct current is applied between the two electrodes. During the electrospinning and electrostatic spraying process, the electrospun fibers come into contact with the mist particles of the electrostatic spray, forming a nanofiber membrane deposited on the aluminum foil, thereby obtaining a precursor nanofiber membrane / aluminum foil composite. (3) Drying and heat treating the precursor nanofiber membrane / aluminum foil composite to form a porous structure on the surface of the aluminum foil.
9. The method for preparing a porous aluminum foil according to claim 8, characterized in that: The polymer solution is selected from any one of polyvinylidene fluoride PVDF, polyacrylonitrile PAN, polyvinyl pyrrolidone PVP, polystyrene PS, polyvinyl fluoride PTFE, and polychloroprene CR, and the organic solvent is selected from any one of N,N-dimethylformamide DMF, ethanol, acetonitrile ACN, acetone ACE, and cyclopentane sulfone TMS. The mass fraction of the polymer solution is 10-15%.
10. The method for preparing a porous aluminum foil according to claim 8, characterized in that: The nitrate solution includes a solution formed by dissolving any or more of copper nitrate, gallium nitrate, bismuth nitrate, zinc nitrate, aluminum nitrate, germanium nitrate, cobalt nitrate, manganese nitrate, molybdenum nitrate, and nickel nitrate in an alcohol solution, and the alcohol solution is selected from ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, butanetriol, sec-butanol, and tert-butanol.
11. The method for preparing a porous aluminum foil according to claim 8, characterized in that: The electrospinning solution is placed in a syringe, and the spinning conditions are: spinning at a temperature of 40-55°C, a humidity of 35-45%, a voltage of 12-18 kV, and a receiving distance of 10-18 cm, and electrospinning for 10-24 hours; The electrostatic spray solution is placed in a syringe, and the spraying conditions are: temperature of 40-55°C, humidity of 35-45%, electrostatic spraying at a voltage of 12-18 kV, and a receiving distance of 10-18 cm, and the electrostatic spraying is performed for 10-24 hours.
12. The method for preparing a porous aluminum foil according to claim 8, characterized in that: The heat treatment is pre-sintering in air atmosphere at 1-3 ℃ min -1 The heating rate is 250-300 °C for 1-3 hours, and then heated at 3-5 °C min in an argon atmosphere. -1 The heating rate is 600-800℃ and calcined for 2-5 hours.
13. The method for preparing a porous aluminum foil according to claim 12, characterized in that: During the sintering process, the nanofiber membrane / aluminum foil composite material is clamped by a graphite plate for heat treatment.
14. A counter electrode for a lithium battery, characterized in that: The porous aluminum foil is prepared by the preparation method described in any one of claims 1 to 7 or 8 to 13.
15. A lithium battery, comprising a lithium sheet and a separator, characterized in that: It also includes a porous aluminum foil prepared by the preparation method according to any one of claims 1-7 or 8-13 as a counter electrode and is arranged below the diaphragm.